Petrography and geochemistry of the granitoids and associated volcanic rocks of the northern part of Kushaka and Birnin Gwari schist belts, NW Nigeria: implications for provenance and geological setting - Oluyede, Kehinde; Garba, Ibrahim; Danbatta, Umar; Ogunleye, Paul; Klötzli, Urs (International Journal of Advanced Geosciences, 2021)
The granitoids and the associated volcanic rocks of the northern part of Kushaka and Birnin Gwari schist belts were emplaced in the ca. 3.5 â€“ 1. 0 Ga remobilized basement complex terrain composed of metasedimentary and metaigneous rocks that later underwent medium- to high-grade metamorphism during the Pan-African thermo-tectonic event. They comprise dominantly of diorite, granodiorite, granite, granite gneiss and basalt, and are product of metasomatism and injections. The diorite and granodiorite occur as paleosome and the granite as leucosome with the development of high temperature minerals, locally attaining granulite facie metamorphism. Plagioclase, biotite, hornblende, pyroxene and olivine fractionation played an important role during their genesis through fractional crystallization of basaltic magma and partial melting of older dioritic-granodioritic source rock in the deep crust which were themselves ultimately derived through fusion of mantle materials contaminated by continental crust and enriched by fluids derived from oceanic crust in an arc setting. Geochemical characteristics have revealed different chemical trends in granitoids and basalts. The granitoids are calc-alkaline, ferroan and magnesian, metaluminous and peraluminous in character. They also exhibit I- and S-type signatures with enrichment in LILE, radioelements (Th and U), depletion in Nb, Sr, P and Ti, high LREE fractionation factors (La/Yb) (1.05 to 77.20), and pronounced negative Eu anomalies (Eu/Eu* = 0.34 to 1.10). Similar patterns of spidergrams show that the rocks are genetically related and were emplaced in a volcanic arc and syn-collisional setting. The basalt is tholeiitic, metaluminous and high in Fe and Mg with relative enrichment in LILE, HFSE, low and near flat LREE and HREE, low fractionation [(La/Yb)N = 1.4] with Eu/Eu* value of 1.10. It is evidently a back arc cum mid-ocean ridge (MORB) basalt. The consistent decrease in the content of MgO, Fe2O3 MnO, CaO, Sc, Cr and V of the basalt, diorites, granodiorites, and granites indicates continuous igneous crystallization process. It seems that extrusion of basaltic magmas from the sub-circular Kushaka Complex derived from subduction of oceanic crust resulted in complete change in the genesis of the magmas at the time, in this region. The granitoids and the basalt may have formed behind subducted Pan-African plate due to effects of compressional and tensional forces caused by oceanic plate roll-back which resulted to a zone of extension, parallel to the island arc. The granitoids present similar chemical characteristics to those in the other areas underlain by the basement complex and schist belts in the north and eastern parts of the Pan-African mobile belt, while basalts are similar to ophiolites and amphibolites in other schist belts of Nigeria forming a lateral continuation of the same mobile belt.Â